(untitled) (Applied Biological Research, 2011)
An experiment was conducted to assess the effect of Bhringraj (Eclipta alba) herb supplementation to bajra straw @ 0, 1, 2, 3 and 4% kg-1 dry matter substrate on degradability of dry matter (DM), organic matter (OM) and neutral detergent fibre (NDF) and total gas production (TGP) using goat rumen liquor. Significant improvement in nutrient degradability of DM, OM and NDF in bajra straw and TGP production was observed due to Bhringraj supplementation with maximum values at 3% kg-1 DM. Another in vitro trial was performed to evaluate the effect of 3% Bhringraj kg-1 DM on rumen fermentation characteristics in complete feed having bajra straw and concentrate mixture in 60:40 ratio. The treatment significantly improved nutrient degradability (DM, OM and NDF), TGP, total rumen nitrogen and TVFA in comparison to control. Addition of Bhringraj in complete feed did not alter rumen pH, however there was significant decrease in rumen ammonia nitrogen in herb supplemented complete feed.